MicroRNA‐223 Ameliorates Nonalcoholic Steatohepatitis and Cancer by Targeting Multiple Inflammatory and Oncogenic Genes in Hepatocytes. Issue 4 (5th June 2019) - He, Yong; Hwang, Seonghwan; Cai, Yan; Kim, Seung‐Jin; Xu, Mingjiang; Yang, Dingcheng; Guillot, Adrien; Feng, Dechun; Seo, Wonhyo; Hou, Xin; Gao, Bin
Abstract : Nonalcoholic fatty liver disease (NAFLD) represents a spectrum of diseases ranging from simple steatosis to more severe forms of liver injury including nonalcoholic steatohepatitis (NASH), fibrosis, and hepatocellular carcinoma (HCC). In humans, only 20%‐40% of patients with fatty liver progress to NASH, and mice fed a high‐fat diet (HFD) develop fatty liver but are resistant to NASH development. To understand how simple steatosis progresses to NASH, we examined hepatic expression of anti‐inflammatory microRNA‐223 (miR‐223) and found that this miRNA was highly elevated in hepatocytes in HFD‐fed mice and in human NASH samples. Genetic deletion of miR‐223 induced a full spectrum of NAFLD in long‐term HFD‐fed mice including steatosis, inflammation, fibrosis, and HCC. Furthermore, microarray analyses revealed that, compared to wild‐type mice, HFD‐fed miR‐223 knockout (miR‐223KO) mice had greater hepatic expression of many inflammatory genes and cancer‐related genes, including (C‐X‐C motif) chemokine 10 ( Cxcl10 ) and transcriptional coactivator with PDZ‐binding motif ( Taz), two well‐known factors that promote NASH development. In vitro experiments demonstrated that Cxcl10 and Taz are two downstream targets of miR‐223 and that overexpression of miR‐223 reduced their expression in cultured hepatocytes . Hepatic levels of miR‐223, CXCL10, and TAZ mRNA were elevated in human NASH samples, which positively correlated with hepatic levels of several miR‐223 targeted genes as well as several proinflammatory, cancer‐related, and fibrogenic genes. Conclusion: HFD‐fed miR‐223KO mice develop a full spectrum of NAFLD, representing a clinically relevant mouse NAFLD model; miR‐223 plays a key role in controlling steatosis‐to‐NASH progression by inhibiting hepatic Cxcl10 and Taz expression and may be a therapeutic target for the treatment of NASH.